Ectophoma salviniae sp. nov., Neottiosporina mihintaleensis sp. nov. and four other endophytes associated with aquatic plants from Sri Lanka and their extracellular enzymatic potential - Madhara K. Wimalasena; Madhara K. Wimalasena; Madhara K. Wimalasena; Nalin N. Wijayawardene; Nalin N. Wijayawardene; Nalin N. Wijayawardene; Thushara C. Bamunuarachchige; Gui-Qing Zhang; R. G. Udeni Jayalal; Darbhe J. Bhat; Darbhe J. Bhat; Turki M. Dawoud; et al. (Frontiers in Cellular and Infection Microbiology)
Endophytic fungi associated with selected aquatic plants, Eichhornia crassipes, Nymphaea nouchali, Salvinia minima and S. molesta were evaluated. Ectophoma salviniae sp. nov. and Neottiosporina mihintaleensis sp. nov. are introduced as novel taxa from Salvinia spp. from Sri Lanka. Chaetomella raphigera is reported as a new geographical record, Colletotrichum siamense and C. truncatum are reported as novel host records in aquatic plants, while Phyllosticta capitalensis has been identified on the same host (Nymphaea nouchali) in the North-Central Province of Sri Lanka. Identification of the fungi was based on morphological characteristics and multi-locus phylogenetic analyses using ITS, LSU, SSU, ACT, CHS-1, GAPDH, tub2, rpb2, and tef1-α molecular markers. The identified fungi were analysed for extracellular enzymatic properties. According to the qualitative analysis, Ectophoma salviniae sp. nov. exhibited the highest amylase production, Chaetomella raphigera exhibited the highest cellulase enzyme production, and Neottiosporina mihintaleensis sp. nov. exhibited the highest laccase production. The results demonstrate the aquatic fungal diversity in this region and their extracellular enzymatic potentials, providing valuable insights for future biotechnological approaches.